In Vivo Application and Tracking of Baculovirus - J. Airenne, Kari; Makkonen, Kaisa-Emilia; J. Mahonen, Anssi; Yla-Herttuala, Seppo (Current Gene Therapy, 2010)
Baculoviruses are safe and high-capacity vectors for gene delivery which have matured from the initial successful experiments performed in liver cells into convenient tools to transduce almost any cell from any origin in vitro and ex vivo. This is a result of 15 years of intensive vector development as well as studies performed in vertebrate cells to reveal important factors affecting the transduction efficacy. Now, at the stage when the first evidence of meaningful use of baculoviruses for therapeutic applications has been reported, there is no doubt that the technology will meet the expectations as highly useful platform for many applications of gene delivery. This review summarizes the pre-clinical in vivo work carried out with baculoviruses and discusses remaining challenges which still need to be solved.
Keywords: BacMam